Effect of Ceramic Thickness and Adhesive Light Curing on Bond Strength of Resin Cements to Enamel - Alvarenga, Hillary; Baroudi, Kusai; Shetty, Raghavandra M.; Berdouses, Elias D.; Oliveira, Marianna Pires de; Diniz, Anna Laura; Ferreira, Gabriel; Silva-Concilio, Laís Regiane; Amaral, Marina (European Journal of Dentistry, 2025)
Objectives For cementation of ceramic restorations, a layer of adhesive followed by resin cement is applied to the treated enamel surface. The light activation of adhesive may occur before or simultaneously with the resin cement. The aim of this study was to evaluate the influence of ceramic thickness and previous light activation of adhesive on shear strength of resin cement to enamel.Materials and Methods Vestibular bovine enamel was bonded to lithium disilicate ceramic cylinders with resin cement. The samples were divided into two groups, according to the ceramic thickness (1 or 2 mm). The cylinders had one surface treated for cementation and the enamel surface was treated with acid etching and adhesive system. Only half of samples received light activation of the adhesive prior to cementation. The samples were stored for 30 days in water at 37°C, and then subjected to the shear bond strength test.Statistical Analysis Two-way analysis of variance was applied to evaluate the influence of previous light activation and ceramic thickness on the bond strength to enamel (α = 0.05).Results The results of this study indicated that there is no significant difference in the shear adhesive strength between ceramics and dental enamel in relation to the factors evaluated.Conclusion It is concluded that bond strength is not affected by neither the previous adhesive light activation nor ceramic thickness (1 or 2 mm).
Keywords: laminate veneers; cementation; shear strength